Pulmonary cryptococcosis manifesting as diffuse air-space consolidations in an immunocompetent patient - Choi, Hye Won; Chong, Semin; Kim, Mi Kyung; Park, In Won (Journal of Thoracic Disease, 2017)
Pulmonary cryptococcosis is an opportunity infection commonly occurred in the immunocompromised patients. However pulmonary cryptococcosis in the immunocompetent was reported up to 35% and these cases tend to show confined and localized radiologic findings than in immunocompromised patients. To our knowledge, extensive air-space consolidations have not frequently occurred in the immunocompetent patient. Therefore, in this case, we report a rare case of a 73-year-old woman who was diagnosed with pulmonary cryptococcosis, manifesting as diffuse air-space consolidations even though normal immune status. Thus, the possibility of pulmonary cryptococcosis should be considered when a patient with a normal immune status presents without respiratory symptoms are accompanied by consolidation on imaging.